A field study of the fate of biosolid-borne silver in the soil-crop system. (April 2020) - Yang, Lu; Li, Simin; Wu, Longhua; Ma, Yibing; Christie, Peter; Luo, Yongming
Abstract: Land application of biosolids is a major route for the introduction of silver (Ag) into the terrestrial environment. Previous studies have focused on the risks from Ag to the human food chain but there is still a lack of quantitative information on the flow of biosolid-borne Ag in the soil-crop system. Two long-term field experiments were selected to provide contrasting soil properties and tillage crops to investigate the fate of Ag from sequentially applied biosolids. Biosolid-borne Ag accumulated in the soil and < 1‰ of applied Ag was taken up by the crops. The biosolid-borne Ag also migrated down and accumulated significantly (p < 0.05) in the soil profile to a depth of 60–80 cm at an application rate of 72 t biosolids ha −1 . Soil texture significantly affected the downward transport of biosolid-borne Ag and the migration of Ag appeared to be more pronounced in a soil profile with a low clay content. Moreover, loss of Ag by leaching may not be related to the biosolid application rate. Leaching losses of Ag may have continued for some time after biosolid amendment was suspended. The results indicate that soil texture may be a key factor affecting the distribution of biosolid-borne Ag in the soil-crop system. Graphical abstract: Image 1 Highlights: Soil texture is an important factor in biosolid-borne silver behaviour in soil-crop system. Ag accumulated in the soil after biosolid application. Leaching losses of Ag may not be related to the biosolid application rate. Abstract : Soil texture may be a key factor affecting the downward transport of biosolid-borne Ag but the amount of Ag leached may be unrelated to the biosolid application rate.